Pemahaman Masyarakat Muslim Menengah Kebawah Merespon Gerakan Nasional Non Tunai Bank Syariah - L. M. Ikbal Patoni; Muhammad Rafi’i Sanjani (Jurnal Ilmiah Ekonomi Islam, 2022)
The issues discussed in this study are how the practice of transactions using a non-cash payment system and how the understanding of the lower middle class Muslim community regarding the payment system using non-cash in Islamic Banking in the Kekalik Kebon Community, West Pagesangan Village, Mataram, West Nusa Tenggara. The purpose of this study is to find out the practice of transactions using non-cash payment systems and to find out the understanding of the middle and lower Muslim community regarding payment systems using non-cash. In this study, the researcher used a descriptive qualitative approach, one of the methods used was to conduct interviews. The result is that most of the lower middle class Muslim community have known, used, and understood non-cash payment instruments as an alternative to cash. Factors that encourage and motivate people to use non-cash payment instruments include security, convenience, speed, and efficiency factors. However, the public still does not fully understand the non-cash payment system due to the lack of direct information and the lack of direct socialization in the Kekalik Kebon Community, West Pagesangan Village, Mataram, West Nusa Tenggara. This non-cash payment system is very useful for the community in conducting transactions if they are in a different place, because they do not require additional money to meet. The public only knows the term for transacting at ATMs but does not know the term at all about the National Non-Cash Movement. Actually, if people understand more about the National Non-Cash Movement This will make it easier for people to carry out transactions directly in their daily lives.